2017
DOI: 10.1161/circulationaha.116.023712
|View full text |Cite
|
Sign up to set email alerts
|

Mediterranean Diet Improves High-Density Lipoprotein Function in High-Cardiovascular-Risk Individuals

Abstract: URL: http://www.controlled-trials.com. Unique identifier: ISRCTN35739639.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
148
3
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 187 publications
(160 citation statements)
references
References 48 publications
7
148
3
2
Order By: Relevance
“…Among factors which can modify CEC and HDL characteristics, besides VOO alone, we have reported that diets rich in VOO and antioxidants such as the Mediterranean diet have shown to increase the CEC together with improvements in HDL oxidative status, composition, ApoA‐I, and HDL particle size . Also, novel pharmaceutical approaches are being developed for improving HDL characteristics and functionality.…”
Section: Discussionmentioning
confidence: 99%
“…Among factors which can modify CEC and HDL characteristics, besides VOO alone, we have reported that diets rich in VOO and antioxidants such as the Mediterranean diet have shown to increase the CEC together with improvements in HDL oxidative status, composition, ApoA‐I, and HDL particle size . Also, novel pharmaceutical approaches are being developed for improving HDL characteristics and functionality.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, men who adhered to a “prudent” diet (consisting of vegetables, fruits, whole grains, fish and poultry) have half the CVD risk of men on a “Western” diet (red meat, processed meat, refined grains, sweets and dairy products). 172 Similarly, in the PREDIMED trial in which 7447 persons were followed for 4.8 years, a Mediterranean diet supplemented with extra-virgin olive oil or nuts improved the atheroprotective effects of HDL 173 , delayed atherogenesis 174 , and reduced the incidence of major cardiovascular events (HR=0.7), 175 further underscoring the profound influence of diet on CVD risk and outcomes.…”
Section: The Personal Environmentmentioning
confidence: 97%
“…Only increases in the intake of polyphenol‐rich virgin olive oil (25 mL d –1 ), a lycopene‐rich diet, and a traditional Mediterranean diet have been reported to enhance HDL functions in clinical trials. Regarding the Mediterranean diet, our research group has demonstrated that adherence to this dietary pattern (associated with a high intake of virgin olive oil, nuts, fruit, vegetables, legumes, and whole grains, and a moderate consumption of fish and wine with meals) improved several HDL functions: it promoted cholesterol efflux capacity (their capacity to pick up cholesterol), HDL ability to esterify cholesterol (necessary for the effective transport of cholesterol in these lipoproteins), paraoxonase‐1 activity (PON1, a key HDL‐bound antioxidant enzyme), and HDL capacity to promote endothelial release of nitric oxide, and decreased the activity of the cholesteryl ester transfer protein (CETP, pro‐atherogenic when excessively active) . The food items individually responsible for such effects (within the context of a healthy dietary pattern such as this or others), however, remain to be elucidated.…”
Section: Introductionmentioning
confidence: 99%